(untitled) (Costos y Gestión, 2021)
The work presents the case of an Argentine SME, dedicated to the production and marketing of automotive accumulators, framed in strategic cost management. The market opportunities and the entrepreneurial profile of the owners, leads them to evaluate a strategic reformulation based on a strong increase in fixed costs that will allow to efficient production, reducing variable costs, improving processes, reducing waste and obtaining a decommoditized product. This will result in a quantum leap in the positioning of the SME, preventing the rest of the competitors from reaching it in the medium term, achieving a competitive advantage in the sector. Traditional tools such as the degree of operational lever were first used to assess the decision, however when we subject the analysis to models that measure the value added by the strategy to the SME, the results are very different, even contradictory. Through case analysis, the work aims to generate a contribution to the strategic cost management of closed capital SMEs, whose investments are tied to financing as they are developed in contexts with rationing funds, and in uncertain scenarios, proposing a five-step model (based on the flow of discounted funds), which allows to calculate the impact that the strategy of dismodilization of products generates on the value of SMEs. Obviously, the measurement of the value created will vary from one SME to another, depending on the driving style, human resources, the nature and diversity of the business portfolio, the degree of decentralization of its size, its coverage, its clientele and the sense of urgency that exists in it; however, a tool that measures strategic impact will help make more rational decisions with more efficient allocation of resources.